PENGARUH TECHNOLOGY READINESS PADA ATTITUDE, SUBJECTIVE NORM, DAN PERCEIVED BEHAVIOR CONTROL DAN PENGARUHNYA PADA NIAT BELI ONLINE - Randi, Ahmad Randi Azwar; Prihatiningrum, Raden Roro Yulianti (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
The purpose of this study was to examine and analyze the effect of Technology Readiness on Attitude, Subjective Norms, and Perceived Behavior Control and its Effect on Online Purchase Intention. This type of research is included in explanatory research. The population is visitors to Tokopedia through the website or application. Sampling technique with purposive sampling. Data analysis uses partial least square with the help of Smart-PLS 3.0 program. Hypothesis test results are known that technology readiness affects attitude and subjective norm while perceived behavioral control has no effect. Attitude, subjective norm and perceived behavioral control have an influence on purchase intention. The conclusion of this research is Attitude and subjective norm influenced by Technology readiness has an influence on purchase intention and technology readiness has no influence on perceived behavioral control.